2021
DOI: 10.1167/iovs.62.6.9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics in Glaucoma: A Systematic Review

Abstract: PURPOSE. Glaucoma remains a poorly understood disease, and identifying biomarkers for early diagnosis is critical to reducing the risk of glaucoma-related visual impairment and blindness. The aim of this review is to provide current metabolic profiles for glaucoma through a summary and analysis of reported metabolites associated with glaucoma. METHODS.We searched PubMed and Web of Science for metabolomics studies of humans on glaucoma published before November 11, 2020. Studies were included if they assessed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 59 publications
3
18
0
1
Order By: Relevance
“…Of note, the systematic review identified 12 metabolites that have been identified across the various metabolomics studies as being associated with open-angle glaucoma in at least 2 studies; of these, two were phospholipids (PCs), 2 were organic acids and derivatives (including amino acids), and 2 were carnitines. 9 Our results are consistent with prior studies in identifying phospholipids and various organic acids and derivatives in both the NHS/NHS2/HPFS and UK Biobank, while also showing support for the role of lipids, particularly diglycerides, triglycerides and other lipids (e.g., cholesteryl esters).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Of note, the systematic review identified 12 metabolites that have been identified across the various metabolomics studies as being associated with open-angle glaucoma in at least 2 studies; of these, two were phospholipids (PCs), 2 were organic acids and derivatives (including amino acids), and 2 were carnitines. 9 Our results are consistent with prior studies in identifying phospholipids and various organic acids and derivatives in both the NHS/NHS2/HPFS and UK Biobank, while also showing support for the role of lipids, particularly diglycerides, triglycerides and other lipids (e.g., cholesteryl esters).…”
Section: Discussionsupporting
confidence: 91%
“…However, LPCs are proinflammatory and pro-oxidant, 53 and they may play a role in the autotaxin-lysophophatidic acid pathway in intraocular pressure regulation. 35,37,[54][55][56][57] Our results are consistent with other targeted lipidomic studies of glaucoma that have revealed higher specific phospholipids in blood, 9 the trabecular meshwork or aqueous humor of glaucomatous eyes. 55,56,58,59 Mitochondrial dysfunction, carnitines and organic acids and derivatives Mitochondrial dysfunction has been hypothesized as a key component of POAG pathophysiology.…”
Section: Phospholipidssupporting
confidence: 90%
See 2 more Smart Citations
“…There are several reviews concerning the application of metabolomics in glaucoma [113,114] and studies of glaucoma based on a metabolomics approach. We retrieved 16 full-text articles in the area of clinical metabolomics from the PubMed database (Table 4).…”
Section: Glaucomamentioning
confidence: 99%